On Marx : revolutionary and utopian - Ryan, Alan (Liveright Publishing, 2014)
In On Marx, Alan Ryan examines Marx's writing, not within the framework of Lenin or Tolstoy but within its own time, tracing its Hegelian roots and providing a sterling explication and critique of his theories of alienation, class struggle and revolution. This volume provides the clearest, most accessible introduction to Marx's theories in recent years. On Marx features a chronology, biography and excerpts from Marx's major works.